Fishes (raw and cooked) Fatty acid profile consumed in Bahrain - Halit, Arik; Ozcan, Kazim (Advances in Aquaculture and Fisheries Management, 2014)
The objective of this study was to determine the fatty acid profile of raw and cooked (grilled, curried and fried) fish commonly consumed in Bahrain. Four most popular species of fish were purchased from the local market in Manama city, the capital of Bahrain. Fatty acids in raw and cooked fish were separated and quantitatively determined by gas liquid chromatography (GLC) using standard methods. The findings revealed that the predominant fatty acids in raw fish were palmitic, stearic, oleic, palmitoleic and linoleic acid (30.5 to 30.50, 3.6 to 8.8, 13.4 to 22.6, 6.7 to 14.1 and 1.3 to 2.0 mg/100 g respectively). With regard to cooking, curried and fried Pearlspotted Rabbitfish showed predominant changes in their fatty acid profiles. In the omega-3 and omega-6 families the dominant fatty acids were eicosapentaenoic acid (EPA) (2.9 to 6.4 mg/100 g), docosahexaenoic acid (DHA) (1.5 to 14.8 mg/100 g) and arachidonic acid (AA) (2.0 to 5.2 mg/100 g). There was no consistent trend in the EPA/DHA ratio in all the four species of fish. Cooking increased polyunsaturated fatty acid (PUFA), the most noticeable increase was again in Pearlspotted Rabbitfish. PUFA increased from 21.8 mg/100 g to 50.0 mg/100 g in curried and 49.5 mg/100 g in the fried variety.